A critical analysis on the role of outsourcing practice in ensuring organizational performance: the case of DHL Harare International Airport, (2013-2015) - George, Rodney L. (Midlands State University, 2017)
The main objective of this research was to explore motives, benefit, challenges and strategies for ensuring success of outsourcing at DHL Harare International Airport. Specific objectives were to explore the organizational determinants or motivators for outsourcing, to investigate on the benefits and opportunities arising out of outsourcing, to examine the challenges and risks that affect outsourcing and to establish the critical success factors of outsourcing. The researcher reviewed literature on motivation for outsourcing, benefits, problems faced and measure for ensuring success. Information was collected from both managers and general employees at DHL Harare International Airport. Census sampling technique was used to select all the 34 participants from all the four department which includes procurement, clearing, finance and operations. The study found out that DHL Harare International Airport outsource activities like customs clearing, transport, security and IT. Reasons for outsourcing include the need to focus on DHL’s key competencies, need for flexibility and need to use specialized skills. As a result of outsourcing, managers are able to concentrate on strategic planning and management because other responsibilities are shifted to more skilled personals who are able to do it professionally. Some of the negative effects of outsourcing include transfer of knowledge, poor quality, hidden cost, loss of innovation, risking internal security and altering of information. The study pointed out that, to ensure success of outsourcing, transparency is vital, accountability is important, and there is also a need for effective communication. The researcher recommended that there was need for adoption of professional procurement practices and the other recommendation was the need to train procurement officers. In addition, there was a need to decentralize procurement so that decisions can be made in time. In having a centralized procurement policy has not managed to prevent corruption, but has actually perpetuated it. The researcher recommended further studies to be conducted on issue of outsourcing. This was due to fact that this study focused on DHL Harare International Airport only. A more encompassing study by a research institute would be desirable.